Re-development of a Mughal mosque Andarkilla mosque & market complex Andarkilla, Chittagong - Abadin, Joynal (BRAC University, 2017)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2016.